Therapy with canakinumab for adult-onset still's disease - E. L. Nasonov (Научно-практическая ревматология, 2019)
Still's disease in children (systemic-onset juvenile idiopathic arthritis, SoJIA) and in adults (adult-onset Still's disease) are considered as non-familial systemic autoinflammatory diseases of unknown etiology driven by similar immunopathogenetic mechanisms. The adult-onset Still's disease pathogenesis is based on genetically determined innate immunity disturbances and molecular basis of immunopathogenesis consists of NLRP3 inflammasomedependent mechanisms of inflammation characterized by hyperproduction of proinflammatory cytokines interleukin (IL) 1 and IL18. Nonsteroidal anti-inflammatory drugs, glucocorticoids, methotrexate and other disease modifying drugs are considered as «first line» medications for the treatment of adult-onset Still's disease and if they fail biologicals are recommended. A review of the literature data concerning anti-IL1 monoclonal antibodies administration in adult-onset Still's disease is presented, indicating good prospects for the use of canakinumab not only in case of resistance to standard therapy, but also as a «first-line» therapy in the onset of the disease.